Frank Einstein and the Electro-Finger - Scieszka, Jon (Scieszka, Jon. Frank Einstein, 2015)
"Frank Einstein (kid-genius scientist and inventor) and his best friend, Watson, along with intelligent robots Klink and Klank once again find themselves in competition with T. Edison, their classmate and archrival--this time in the quest to unlock the power behind the science of energy"--